2022
DOI: 10.1037/xap0000362
|View full text |Cite
|
Sign up to set email alerts
|

Improving the interpretation of verbal eyewitness confidence statements by distinguishing perceptions of certainty from those of accuracy.

Abstract: When an eyewitness makes an identification from a lineup, police are also instructed to collect a verbal expression of confidence. This recommendation hinges on the assumption that evaluators will perceive confidence in the manner the witness intended. However, research has consistently shown that these interpretations can be biased by accompanying contextual information. For example, statements that reference facial features (e.g., “I’m very sure. I remember his eyes.”) are perceived as less confident than wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…But if that feature does not distinguish the suspect from the other lineup members (e.g., all lineup members appear to have typical eyebrows), perceptions of suspect-identification accuracy decrease. In other words, if laypersons have a disfluent experience when assessing the validity of a featural justification, it decreases their perceptions of suspect-identification accuracy (Cash & Lane, 2017; Grabman et al, 2022). This is although these featural justifications are often associated with higher levels of accuracy (Dobolyi & Dodson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…But if that feature does not distinguish the suspect from the other lineup members (e.g., all lineup members appear to have typical eyebrows), perceptions of suspect-identification accuracy decrease. In other words, if laypersons have a disfluent experience when assessing the validity of a featural justification, it decreases their perceptions of suspect-identification accuracy (Cash & Lane, 2017; Grabman et al, 2022). This is although these featural justifications are often associated with higher levels of accuracy (Dobolyi & Dodson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The results reported in this study are theoretically interesting, but from an applied perspective, this machine-learning methodology may prove useful to those who work in the criminal justice system and must evaluate eyewitnesses' verbal confidence statements. Although we and others (e.g., Behrman & Richards, 2005;Mansour, 2020) have found that verbal confidence statements are informative of identification accuracy, people often have trouble accurately interpreting them (e.g., Dodson & Dobolyi, 2015;Dobolyi & Dodson, 2018;Grabman et al, 2021). This machine-learning methodology may minimize this problem by providing people a more accurate interpretation of eyewitness confidence statements.…”
Section: Applied Implicationsmentioning
confidence: 95%
“…Decades of laboratory research demonstrate numerous problems in understanding someone’s verbal expression of confidence (e.g., Budescu et al, 2014). We know of several cognitive biases that cause people to misinterpret eyewitness confidence statements specifically (e.g., Cash & Lane, 2017, 2021; Dodson & Dobolyi, 2015, 2017; Grabman et al, 2021; Grabman & Dodson, 2019; Slane & Dodson, 2019). If actors within the criminal justice system misinterpret an eyewitness confidence statement, they can jeopardize innocent suspects and safeguard guilty suspects.…”
Section: The Current Studymentioning
confidence: 99%
“…The difficulty of interpreting eyewitness confidence statements is further exacerbated when additional contextual information is presented. Some factors that have been shown to influence the translation of confidence statements include the lineup fairness (Cash & Lane, 2017), knowledge or suspicion that the witness identified the suspect or a filler (Grabman et al, 2022; Quigley‐McBride & Wells, 2023), and identification decisions made by other witnesses (Slane & Dodson, 2019). Another well documented finding is that statements that include some sort of justification (e.g., “I remember his eyes”) tend to make interpreting eyewitness confidence statements less straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…Another well documented finding is that statements that include some sort of justification (e.g., “I remember his eyes”) tend to make interpreting eyewitness confidence statements less straightforward. Research on the featural justification effect typically shows that featural justifications, coupled with reproductions of the lineup, make people believe the witness is less confident and credible (e.g., Cash & Lane, 2017, 2021; Dobolyi & Dodson, 2018; Dodson & Dobolyi, 2015, 2017; Grabman et al, 2022; Grabman & Dodson, 2019; Slane & Dodson, 2019). This wariness likely stems from an unconscious assessment regarding the type of cues that evaluators expect witnesses to rely upon when providing these judgments.…”
Section: Introductionmentioning
confidence: 99%